Opportunities for Simplification in the Personal Income Tax Systems of the Visegrad Countries - Szabóné Bonifert, Éva (Public Finance Quarterly, 2020)
Due to the numerous factors that can influence the impact of the tax system and redistribution, there is no single correct answer to the question of which composition of economic policy instruments needs to be applied to achieve a desired redistributive effect. The general aim of the study is to investigate in relation to the quantifiable parameters of income tax systems, whether the consideration of the aspects of fairness and justice does have an excessively negative effect on the simplicity of tax systems. The study investigates the possibilities of simplifying the personal income tax system’s composition in some Central and Eastern European countries, while tax burden curves of the system remain as constant as possible. To this end, the study sets up a theoretical, simplified tax model, the parameters of which are determined by a computer program, in order to generate tax burden curves corresponding most closely to the curves of the real tax system. Based on the analysis, it can be established that the theoretical system – in some cases with restrictions – provides a good approximation to the tax burden curves of the investigated countries. The chosen simple model has a good degree of approximation to a real system that does not have significant breakpoints in its tax burden curves, nor does it use a taxation method that fundamentally modifies the system (e.g., splitting). Practical examples help to understand that a complex personal income tax system in a given country is not necessarily the only possible solution to achieve a given tax burden curve, the function may be reproduced with a good approximation constructed from simpler basic elements.